Clinical Value of Combined Multi-Indicator Tests in Diagnosis of Benign Ovarian - Yang L; Du L; Hou B; Niu X; Wang W; Shen W (International Journal of General Medicine, 2023)
Lunyun Yang,1 Lin Du,2 Bailong Hou,1 Xiaoqin Niu,1 Wei Wang,1 Weifeng Shen1 1Department of Laboratory Medicine, The Affiliated Hospital of Jiaxing University, Jiaxing, 314000, People’s Republic of China; 2The Third Xiangya Hospital of Central South University, Changsha, 430074, People’s Republic of ChinaCorrespondence: Weifeng Shen, Department of Laboratory Medicine, The Affiliated Hospital of Jiaxing University, No. 1882, Zhonghuan South Road, Nanhu District, Jiaxing, Zhejiang, 314000, People’s Republic of China, Tel +86-18868345828, Email swf15960220793@126.comBackground: To investigate the existence and degree of correlation between benign ovarian tumors and physiological indicators such as reproductive hormones and tumor markers.Methods: A total of 150 patients with benign ovarian tumors admitted to Jiaxing First Hospital between January 1, 2019, and May 30, 2021, were enrolled as research subjects, while 104 healthy women were enrolled in the control group. Comparative analysis of the correlation between the reproductive hormones LH, FSH, T, E2, and the tumor indicators AMH, AFP, CEA, CA125, and CA199 between the groups was performed.Results: There was no statistical difference in LH, FSH, T, AMH, and CEA expression levels between the experimental and control groups (p≥ 0.05); E2, CA125, and CA199 levels were higher significantly in the experimental group than in the control group (P< 0.001); AFP levels were significantly lower in the experimental group than in the control group (P< 0.05). CA125 (0.762) had the highest AUC when diagnosing the value of each index of E2, CA125, and CA199 for benign ovarian tumors. CA125 had the highest sensitivity (56.7%), followed by E2 (50.0%); CA199 had the highest specificity (84.5%), followed by CA125 (83.7%). The combined diagnosis of benign ovarian tumors was performed using different combinations of the indicators. When the two indicators were combined for diagnosis, the combination of E2 + CA199 had the highest sensitivity (82.6%), whereas the combination of CA125 + CA199 had the largest AUC (0.783) and the highest specificity (86.4%). The combined diagnosis of E2+CA125+CA199 had a higher AUC than the combined diagnosis of the two indicators (0.805), with a sensitivity of 77.2%, and a specificity of 70.9%.Conclusion: The most relevant factors for benign ovarian tumors are E2, CA125, and CA199 and the combination of these three indicators has the highest AUC for disease prediction while increasing the detection rate of benign ovarian tumors.Keywords: benign ovarian tumors, tumor markers, reproductive hormones